Diamond formation from methane hydrate under the internal conditions of giant icy planets - Hirokazu Kadobayashi (Nature Portfolio, 2021)
Abstract Hydrocarbon chemistry in the C–O–H system at high pressure and high temperature is important for modelling the internal structure and evolution of giant icy planets, such as Uranus and Neptune, as their interiors are thought to be mainly composed of water and methane. In particular, the formation of diamond from the simplest hydrocarbon, i.e., methane, under the internal conditions of these planets has been discussed for nearly 40 years. Here, we demonstrate the formation of diamond from methane hydrate up to 3800 K and 45 GPa using a CO2 laser-heated diamond anvil cell combined with synchrotron X-ray diffraction, Raman spectroscopy, and scanning electron microscopy observations. The results show that the process of dissociation and polymerisation of methane molecules to produce heavier hydrocarbons while releasing hydrogen to ultimately form diamond proceeds at milder temperatures (~ 1600 K) and pressures (13–45 GPa) in the C–O–H system than in the C–H system due to the influence of water. Our findings suggest that diamond formation can also occur in the upper parts of the icy mantles of giant icy planets.